Food and Nutrition Security, Agriculture And Climate Change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
On 7 December 2014 Care International, The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and The Technical Centre for Agricultural and Rural Cooperation (CTA) co-organized a seminar on stepping up to address the six issues facing global climate change and food security .The meeting brought together different stakeholders who addressed the issues in breakout sessions. Photos S.Kilungu (CCAFS)